Sperm Concentration, Motility, and Morphology in Subfertile Men - Muzdalifa Mejbel Fedwi; Fadhela Nafaa Kafe; Mariam Ayad Abd (International Journal of Medical Toxicology and Legal Medicine, 2024)
Infertility is a growing global health concernthat affects more than 70 million couples annually. Fifty percent of cases of infertility are caused by male factors, which are mostly caused by deficiencies in sperm quantity and/or quality. This study aimed to analyze sperm morphology, motility, and concentration in subfertile men to understand potential factors contributing to subfertility. A case-control study involving 150 male participants, including 50 fertile men and 100 subfertile men, was conducted. Semen samples were collected and analyzed according to WHO guidelines. Subfertile men showed a significantly lower semen concentration, count, and motility, as well as a lower rate of normal morphological sperm compared to fertile men. There was also a significant association between subfertility and smoking. However, no statistically significant differences were observed in sperm head abnormalities between subfertile and fertile men. These findings suggest that sperm morphology may not be a reliable indicator of subfertility in all cases. Subfertile individuals typically display lower semen parameters.Smoking was identified as a potential contributing factor to male subfertility.